Discovery and SAR of a novel series of potent, CNS penetrant M4 PAMs based on a non-enolizable ketone core: Challenges in disposition. Issue 17 (1st September 2016) - Wood, Michael R.; Noetzel, Meredith J.; Tarr, James C.; Rodriguez, Alice L.; Lamsal, Atin; Chang, Sichen; Foster, Jarrett J.; Smith, Emery; Chase, Peter; Hodder, Peter S.; Engers, Darren W.; Niswender, Colleen M.; et al.
Graphical abstract: Abstract: This Letter describes the chemical optimization of a novel series of M4 PAMs based on a non-enolizable ketone core, identified from an MLPCN functional high-throughput screen. The HTS hit was potent, selective and CNS penetrant; however, the compound was highly cleared in vitro and in vivo. SAR provided analogs for which M4 PAM potency and CNS exposure were maintained; yet, clearance remained high. Metabolite identification studies demonstrated that this series was subject to rapid, and near quantitative, reductive metabolism to the corresponding secondary alcohol metabolite that was devoid of M4 PAM activity.